Seven Things Every Information Professional Needs to Know About Consumer Technologies - Bengtson, Jason A. (My University, 2014)
The consumer space has, in recent years, greatly surpassed the enterprise space as a place to find the latest trends and innovations. In fact, businesses have increasingly begun to interface actively with consumer computing, with concepts such as Bring Your Own Device (BYOD). Hospital librarians should familiarize themselves with some of the key trends in the consumer space to better engage with their patrons, including physicians bringing their personal devices into the workspace.
Citation: Bengtson, Jason. "Seven Things Every Information Professional Needs to Know About Consumer Technologies." Journal of Hospital Librarianship 14.4 (2014) : 395-401. Print.